Conocemos las teorías sobre el proceso del poblamiento americano - Cruz Elera, Rosa (2019)
The session known as We know the theories about the american population process, belongs to the area of social personnel, taking into account the competence Build Historical Interpretations, mobilizing capabilities critically interprets diverse sources, includes historical time and elaborates explanations on historical processes, which will allow students to achieve performance: Obtains information about the process of the American population and the first bands to the first villages of Peru, through the analysis of short texts, as well as in old buildings or archaeological sites of the town._x000D_ For the development of the session, the pedagogical processes and especially the didactic processes of the social personnel area, such as problematization, information analysis and decision making, will be taken into account._x000D_ The strategies to be used will be relevant, considering the needs and interests of the students, in addition to the rhythms and learning styles according to the third grade students.